Switchable charge injection barrier in an organic supramolecular semiconductor - Gorbunov, Andrey V.; Haedler, Andreas T.; Putzeys, Tristan; Zha, R. Helen; Schmidt, Hans-Werner; Kivala, Milan; Urbanavičiūtė, Indrė; Wübbenhorst, Michael; Meijer, E. W.; Kemerink, Martijn (ACS applied materials & interfaces, 2016)
We disclose a supramolecular material that combines semiconducting and dipolar functionalities. The material consists of a discotic semiconducting carbonyl-bridged triarylamine core, which is surrounded by three dipolar amide groups. In thin films, the material self-organizes in a hexagonal columnar fashion through π-stacking of the molecular core and hydrogen bonding between the amide groups. Alignment by an electrical field in a simple metal/semiconductor/metal geometry induces a polar order in the interface layers near the metal contacts that can be reversibly switched, while the bulk material remains nonpolarized. On suitably chosen electrodes, the presence of an interfacial polarization field leads to a modulation of the barrier for charge injection into the semiconductor. Consequently, a reversible switching is possible between a high-resistance, injection-limited off-state and a low-resistance, space-charge-limited on-state. The resulting memory diode shows switchable rectification with on/off ratios of up to two orders of magnitude. This demonstrated multifunctionality of a single material is a promising concept toward possible application in low-cost, large-area, nonvolatile organic memories.
Gesehen am 03.12.2019